2020
DOI: 10.1152/ajpcell.00065.2020
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase-activating polypeptide-induced PAC1 receptor internalization and recruitment of MEK/ERK signaling enhance excitability of dentate gyrus granule cells

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP; ADCYAP1) is a pleiotropic neuropeptide widely distributed in both the peripheral and central nervous systems. PACAP and its specific cognate PAC1 receptor ( ADCYAP1R1) play critical roles in the homeostatic maintenance of multiple physiological and behavioral systems. Notably, maladaptations in the PACAPergic system have been associated with several psychopathologies related to fear and anxiety. PAC1 receptor transcripts are highly expressed in granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…High levels of PAC1 receptor transcripts in the granule cell layer of the dentate gyrus in the hippocampus were initially determined by in situ hybridization studies (Jaworski and Proctor, 2000;Hannibal, 2002) and hippocampal PACAP hilar mossy neurons were shown to send fiber projections to the DG inner molecular layer (IML) (Condro et al, 2016;Johnson et al, 2020b); hence, there are short PACAPergic synaptic circuits between PACAP-expressing hilar mossy cells and the proximal dendrites on PAC1 receptor expressing DG granule cells. Accordingly, PACAP application to hippocampal dentate gyrus slice preparations increased the excitability of granule cells (Johnson et al, 2020a;Johnson et al, 2020b). In whole-cell recordings in current clamp mode, the granule cells fired tonically in response to suprathreshold 1 second depolarizing current injections; the action potential frequency increased with increasing current intensity (Johnson et al, 2020a;Johnson et al, 2020b).…”
Section: Pacap Increases Granule Cell Excitability Through Endosomal Erk Activationmentioning
confidence: 96%
See 1 more Smart Citation
“…High levels of PAC1 receptor transcripts in the granule cell layer of the dentate gyrus in the hippocampus were initially determined by in situ hybridization studies (Jaworski and Proctor, 2000;Hannibal, 2002) and hippocampal PACAP hilar mossy neurons were shown to send fiber projections to the DG inner molecular layer (IML) (Condro et al, 2016;Johnson et al, 2020b); hence, there are short PACAPergic synaptic circuits between PACAP-expressing hilar mossy cells and the proximal dendrites on PAC1 receptor expressing DG granule cells. Accordingly, PACAP application to hippocampal dentate gyrus slice preparations increased the excitability of granule cells (Johnson et al, 2020a;Johnson et al, 2020b). In whole-cell recordings in current clamp mode, the granule cells fired tonically in response to suprathreshold 1 second depolarizing current injections; the action potential frequency increased with increasing current intensity (Johnson et al, 2020a;Johnson et al, 2020b).…”
Section: Pacap Increases Granule Cell Excitability Through Endosomal Erk Activationmentioning
confidence: 96%
“…Accordingly, PACAP application to hippocampal dentate gyrus slice preparations increased the excitability of granule cells (Johnson et al, 2020a;Johnson et al, 2020b). In whole-cell recordings in current clamp mode, the granule cells fired tonically in response to suprathreshold 1 second depolarizing current injections; the action potential frequency increased with increasing current intensity (Johnson et al, 2020a;Johnson et al, 2020b). PACAP enhanced the excitability of DG granule cells assessed by determining the shift in excitability curves determined by plotting action potential frequency before and in PACAP with increasing current steps.…”
Section: Pacap Increases Granule Cell Excitability Through Endosomal Erk Activationmentioning
confidence: 99%
“…Moreover, the majority of existing hippocampal work has focused on CA1 and CA3, but PAC1R is expressed also in the dentate gyrus ( Jaworski and Proctor, 2000 ; Joo et al, 2004 ). Recent work has shown that PACAP-PAC1R activation drives CREB-mediated transcription and promotes excitability of DG granule cells ( Johnson et al, 2019 ; Johnson R. et al, 2020 ; Johnson R. L. et al, 2020 ).…”
Section: Cellular and Synaptic Physiologymentioning
confidence: 99%
“…Pituitary adenylate cyclase-activating polypeptide (PACAP) is a 38-amino acid pleiotropic peptide known to act as a neurotransmitter, neuromodulator, and neurotrophic factor (Nakamachi et al 2011;Ciranna and Costa 2019;Johnson et al 2020;Gargiulo et al 2020). PACAP consistently exerts protective effects in the nervous system and peripheral organs by mediating various physiological processes (Martinez-Rojas et al 2021;Nonaka et al 2020;Toth et al 2020).…”
Section: Introductionmentioning
confidence: 99%